Research on data transmission based on DDPG algorithm - Yan Danting; Jiao Xinquan (Dianzi Jishu Yingyong)
Aiming at the poor reliability and low transmission rate of the current data transmission system, a data transmission system is designed using FPGA and UDP protocol. The system adopts FPGA as the main controller chip and Flash as the storage medium, and sends commands to control the system through the host computer to access the data, adopts Gigabit Ethernet to be in charge of data communication and command reception, and adds a data retransmission mechanism as well as a flow control module to ensure the high-speed and reliable transmission of data. In order to improve bandwidth utilization and reduce network delay, an improved Deep Deterministic Policy Gradient (DDPG) algorithm is added for congestion control. The experimental test results demonstrate that the algorithm presented in this paper can markedly reduce network latency. The system transmission rate can reach 912 Mb/s, and the system enjoys high reliability, low cost, portability, and practical promotion value. It is also convenient for upgrading and maintenance.